PERAN KOMPETENSI PEDAGOGIK GURU DALAM MENGOPTIMALKAN NILAI AKIDAH AKHLAK UNTUK PENDIDIKAN MORAL SISWA KELAS III DI MIMA 01 K.H SHIDDIQ JEMBER - Nabilla Rizqi Salwa Purwadi; Hairul Huda; Badrut Tamami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of pedagogical competence of Akidah Akhlak teachers in optimizing Islamic values of faith and `morality as the foundation of moral education of third grade students at MIMA 01 K.H Shiddiq Jember. The study departs from the premise that the successful internalization of moral religius values in students is not determined solely by the content of the subject matter, but crucially by the quality of pedagogical competence with which teachers manage the learning process. A descriptive qualitative was employed, with data collected through participatory observation, in depth interviews, and documentation. Informants were purposively selected and included the principal, the Akidah Akhlak teachers, and four students representing clasess III-A through III-D. Data analysis followed the Miles Huberman interactive model. The findings reveal that teacher’s pedagogical competence contributes significantly and systematically across five key dimensions: (1) humanistic understanding of student characteristics ; (2) systematic moral-value-based lesson planning; (3) dialogic and educative instruction using modeling (qudwah), habituation (a’adah), and counselling (mau’izhah); (4) conducive classroom management with an educational reward system; and (5) attitude and moral-value-based assessment. These contributions demonstrably cultivate three moral dimensions in students Moral Knowing, Moral Feeling, and Moral Action as evidenced in concrete behavioral changes in daily life.